2020
DOI: 10.1186/s12902-020-0489-6
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of cardiometabolic risk factors in the military population: a systematic review and meta-analysis

Abstract: Background: Although there are numerous studies on the global prevalence of cardiometabolic risk factors (CMRFs) in military personnel, the pooled prevalence of CMRFs in this population remains unclear. We aimed to systematically review the literature on the estimation of the global prevalence of CMRFs in the military population. Methods: We simultaneously searched PubMed and NLM Gateway (for MEDLINE), Institute of Scientific Information (ISI), and SCOPUS with using standard keywords. All papers published up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 49 publications
0
21
0
2
Order By: Relevance
“…For example, military-related stressors have a relationship with acute cardiac disorders (9). In this regard, increased CVD prevalence as well as its risk factors can be observed in this population (10)(11)(12). Previous studies have found that the prevalence of hypertension and hypertriglyceridemia is 8.8 and 30.5% across the military personnel in Iran (9).…”
Section: Introductionmentioning
confidence: 84%
“…For example, military-related stressors have a relationship with acute cardiac disorders (9). In this regard, increased CVD prevalence as well as its risk factors can be observed in this population (10)(11)(12). Previous studies have found that the prevalence of hypertension and hypertriglyceridemia is 8.8 and 30.5% across the military personnel in Iran (9).…”
Section: Introductionmentioning
confidence: 84%
“…Общая распространенность кардиометаболических ФР ССЗ среди военнослужащих на глобальном уровне с использованием метода метаанализа случайных данных в последних по времени публикациях, для гиперхолестеринемии, гипертриглицеридемии, низкого уровня холестерина липопротеинов низкой плотности и высокого уровня глюкозы в крови натощак составила 21% (17-25), 32% (27-36), 34% (10-57), 24% (16-31), 28% (17-38) и 9% (5)(6)(7)(8)(9)(10)(11)(12), соответственно (в скобках -95% ДИ). Более того, показатели распространенности избыточной массы тела, ожирения, абдоминального ожирения и АГ составляли 35% (31-39), 14% (13)(14)(15)(16), 29% (20-39) и 26% (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), соответственно [18].…”
Section: особенности фр среди военнослужащихunclassified
“…Действие перечисленных обстоятельств усугубляется присутствием индивидуальных ФР, таких как курение, употребление алкоголя, повышенный уровень холестерина, АГ, ожирение, отягощенный наследственный анамнез [5,15,18]…”
Section: приоритеты профилактики ссз среди военно служащихunclassified
“…The military population did not seem to be exposed to CVD, yet published studies on this topic showed that military personnel are equally exposed to CVD as civilians and sometimes even more [16] , [17] . A recent meta-analysis on military population reveals that frequencies of cardiovascular risk factors among soldiers were 26% for hypertension, 9% for hyperglycemia, 14% for obesity, and 35% for overweight [16] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis on military population reveals that frequencies of cardiovascular risk factors among soldiers were 26% for hypertension, 9% for hyperglycemia, 14% for obesity, and 35% for overweight [16] . Another study comparing military personnel to civilians found significant associations between being military personnel and smoking; being military personnel and excessive alcohol consumption; and being veteran and CVD [17] .…”
Section: Introductionmentioning
confidence: 99%